Isolation and identification of aerobic bacteria that cause tonsillitis from patients of Al-Diwaniyah governorate - Ghazi Mahdi, Aamal; Ne’Ama ThuhaibFa’Al; Kalef Mahdi, Rahi (Al-Qadisiyah Journal of Pure Science, 2018)
Tonsillar swab 226 samples were collected from patients who attended to of the E.N.T(Ear,Nose,Throat) ward Al-Diwani ya teaching Hospital and for all ages of that diagonsed based on the symptoms of the infection with Tonsillitis ,bellow the type and precentage of isolated bacteria. %22.87(83/366)Streptococcus pyogenes,%21.03(77/366)Staphlococcus aureus , %18.74(32/366)Corynebacterium pseudodiphtheriticum , %12.29 (45/366) Haemophilus influenzae, %5.46(20/366) Bacillus spp, %4.09(15/366) Lactobacillus, %4.09(15/366) Strepc.pneumoniae. The results showed the dominace of group A Beta haemolytic Streptococci GAS(Group A Streptococci) on other groups since it consituted %66.93 of the total of bHS(Beta Haemolytic Streptococci) strains that consituted %33.87 of the total of isolated bacteria ,followed by (GBS) with a precentage of %13.7 then GDS(Group D Streptococci) %11.29 and GGS %8.06.Furthermore Strepc.pyogenes was found to be the most dominant in case of acute tonsillitis with the precentage %27.65, while Staph.aureus was the most dominant in case of chronic tonsillitis with the precentage %25.28.